Structural performance of composite WikiHouse beams from CNC-cut timber panels. (1st February 2022) - Granello, Gabriele; Reynolds, Thomas; Prest, Clayton
Abstract: Computer-numerical-control (CNC) fabrication of interlocking-plate timber structures is a promising form of construction for housing with the potential to be socially, economically and environmentally sustainable. The primary mechanisms of load transfer in these structures rely on direct contact and friction between interlocking elements, without the nails and screws used in conventional timber structures. The development of these connections is relatively new, and therefore the application of interlocking plates structural systems in real projects is so far limited. In this study, the WikiHouse interlocking-plate timber structural system for digitally fabricated houses is presented from a design and fabrication point of view. The main structural elements of the system, the beams and columns, are hollow section members fabricated using computer-numerical-control (CNC) cut plywood panels. In the first part of the paper, the concept of Wikihouse and its fabrication process are presented. Then, the performance of the structural beams is investigated by means of experimental testing on full scale 5 m specimens. Finally, an analytical model to calculate the beam capacity and displacements is derived based on elastic beam bending and joint flexibility. Results show that the specimens failed in a ductile manner. Furthermore, it was found that the joints between the panels introduce extra flexibility to element, and that rigid-body rotations occurring in the joints within the span make a substantial contribution to the overall deflection. Highlights: A new interlocking-plate system for digitally fabricated timber houses is presented. Beams were tested by means of 4-point bending test on full scale specimens. An analytical model based on beam with rotational springs was derived and calibrated. 3D models and assembly guide are available as supplemental material to this paper.